Effect the Extracts of Some Spice Plants Use in Libyan Households on Germination Growth, Mitosis and the Total Content of Nucleic Acids (RNA-DNA) of a Peas Plant - Elawa, Amal M.; Zuka, Hnan; Amer, Halima (Al-Mukhtar Journal of Sciences, 2008)
This study was conducted to investigate the effect of two herbaceous wild plants that use to give the flavor of the food in addition as Libyan traditional medicine treatments. these plant include, Thyme and Mountain Rosemary, their effects on germination growth process and the total content of Nucleic Acids of Peas plant. The result revealed that the percentages of growth, radical length, wet and dry weight decreased significantly in treated peas plant. that coincided with morphological and genetic results which found the Nucleic acid contents of treated plants less than untreated one, and that could conclude as a result of the toxicity of phenolic materials an aromatic oils that found in the extracts of spice plants that belong to family Lamiaceae, in particular when it used in high amounts.